2019
DOI: 10.3390/jcm8030415
|View full text |Cite
|
Sign up to set email alerts
|

A Culture-Independent Analysis of the Microbiota of Female Interstitial Cystitis/Bladder Pain Syndrome Participants in the MAPP Research Network

Abstract: We surveyed urine microbiota of females diagnosed with interstitial cystitis/bladder pain syndrome (IC/BPS) and matched control participants enrolled in the National Institutes of Health (NIH) Multidisciplinary Approach to the Study of Chronic Pelvic Pain (MAPP) Research Network using the culture-independent methodology. Midstream urine specimens were analyzed with the Plex-ID molecular diagnostic platform that utilizes polymerase chain reaction–electrospray ionization–time-of-flight–mass spectrometry (PCR-ESI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 28 publications
0
55
0
1
Order By: Relevance
“…Despite this, several recent studies on urine have identified clear shifts in the microbial community associated with age (Adebayo et al, 2020; Curtiss et al, 2018; Gottschick et al, 2017; Komesu et al, 2018; Liu et al, 2017b; Pearce et al, 2014), sex (Lewis et al, 2013; Pederzoli et al, 2020; Pohl et al, 2020), urgency urinary incontinence in women (Brubaker et al, 2014; Karstens et al, 2016; Pearce et al, 2014; K. J. Thomas-White et al, 2016), bladder cancer (Bi et al, 2019; Bucević Popović et al, 2018; Chipollini et al, 2020; Hourigan et al, 2020; Liu et al, 2019; Mansour et al, 2020; Pederzoli et al, 2020; Wu et al, 2018), interstitial cystitis (Abernethy et al, 2017; Bresler et al, 2019; Domingue et al, 1995; Meriwether et al, 2019; Nickel et al, 2019, 2016; Siddiqui et al, 2012), neuropathic bladders (Forster et al, 2020; Fouts et al, 2012) and pneumonia (Pierre et al, 2020). However, additional work is needed to identify definitive and mechanistic links between the urine / bladder microbiome, host health, and urinary tract disease.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, several recent studies on urine have identified clear shifts in the microbial community associated with age (Adebayo et al, 2020; Curtiss et al, 2018; Gottschick et al, 2017; Komesu et al, 2018; Liu et al, 2017b; Pearce et al, 2014), sex (Lewis et al, 2013; Pederzoli et al, 2020; Pohl et al, 2020), urgency urinary incontinence in women (Brubaker et al, 2014; Karstens et al, 2016; Pearce et al, 2014; K. J. Thomas-White et al, 2016), bladder cancer (Bi et al, 2019; Bucević Popović et al, 2018; Chipollini et al, 2020; Hourigan et al, 2020; Liu et al, 2019; Mansour et al, 2020; Pederzoli et al, 2020; Wu et al, 2018), interstitial cystitis (Abernethy et al, 2017; Bresler et al, 2019; Domingue et al, 1995; Meriwether et al, 2019; Nickel et al, 2019, 2016; Siddiqui et al, 2012), neuropathic bladders (Forster et al, 2020; Fouts et al, 2012) and pneumonia (Pierre et al, 2020). However, additional work is needed to identify definitive and mechanistic links between the urine / bladder microbiome, host health, and urinary tract disease.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced microbial diversity is evident in patients with IC, and the abundance of lactobacilli was significantly elevated in 90% of IC patients compared with 60% of controls. Another study showed low levels of Corynebacterium and high levels of Lactobacillus gasseri in the urine of BPS patients [ 26 ]. However, the above two studies used midstream urine samples, so the vaginal microbiome may have been contaminated.…”
Section: The Microbiome and Urological Cancermentioning
confidence: 99%
“…Here, we review the role of the microbiome in the field of urology, including studies of prostate cancer, bladder cancer, chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS), interstitial cystitis/bladder pain syndrome (IC/BPS), urgency urinary incontinence/overactive bladder (UUI/OAB), stone disease, and urinary tract infection (UTI) ( Table 1 ) [ 6 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another exploratory study comparatively surveyed the urine microbiota of female patients with interstitial cystitis (IC)/bladder pain syndrome (BPS) and controls who were enrolled in the National Institutes of Health (NIH) Multidisciplinary Approach to the Study of Chronic Pelvic Pain (MAPP) Research Network. It identified potential negative impacts of the presence of Lactobacillus gasseri and protective influence of Corynebacterium [35]. It should be noted that a different study on urinary incontinence (UI) found a lack of Lactobacillus to be associated with urgency UI and resistance to anticholinergic treatments [36].…”
Section: Microbiome Studies In Urological Diseasesmentioning
confidence: 99%